Change Management Analysis Of â€œBerAKHLAKâ€ Policy at Government Owned Corporation - Andi Azikin Idrus; Djoko Triono; Rahmawati Rahmawati (UIN Sunan Gunung Djati, 2024)
This research focuses on analyzing the basic values policy of